Rapid discrimination between clinical Clostridioides difficile infection and colonization by quantitative detection of TcdB toxin using a real-time cell analysis system - Shen, Yuhang; Lin, Shan; You, Peijun; Chen, Yu; Luo, Yun; Song, Xiaojun; Chen, Yunbo; Jin, Dazhi (Frontiers in Microbiology, 2024)
It is important to accurately discriminate between clinical Clostridioides difficile infection (CDI) and colonization (CDC) for effective antimicrobial treatment. In this study, 37 stool samples were collected from 17 CDC and 20 CDI cases, and each sample were tested in parallel through the real-time cell analysis (RTCA) system, real-time PCR assay (PCR), and enzyme-linked immunosorbent assay (ELISA). Notably, RTCA-measured functional and toxical C. difficile toxin B (TcdB) concentrations in the CDI group (302.58 ± 119.15 ng/mL) were significantly higher than those in the CDC group (18.15 ± 11.81 ng/mL) (P = 0.0008). Conversely, ELISA results revealed no significant disparities in TcdB concentrations between the CDC (26.21 ± 3.57 ng/mL) and the CDI group (17.07 ± 3.10 ng/mL) (P = 0.064). PCR results indicated no significant differences in tcdB gene copies between the CDC (774.54 ± 357.89 copies/μL) and the CDI group (4,667.69 ± 3,069.87 copies/μL) (P = 0.407). Additionally, the functional and toxical TcdB concentrations secreted from C. difficile isolates were measured by the RTCA. The results from the CDC (490.00 ± 133.29 ng/mL) and the CDI group (439.82 ± 114.66 ng/mL) showed no significant difference (P = 0.448). Notably, RTCA-measured functional and toxical TcdB concentration was significantly decreased when mixed with pooled CDC samples supernatant (P = 0.030). This study explored the novel application of the RTCA assay in effectively discerning clinical CDI from CDC cases.